Enhancing Employee Performance: The Impact of Quality of Work Life, Organizational Citizenship Behavior, and Work Motivation: Meningkatkan Kinerja Karyawan: Dampak Kualitas Hidup Kerja, Perilaku Kewarganegaraan Organisasi, dan Motivasi Kerja - Audi Sulthan Fadhlurahman; Detak prapanca (Academia Open, 2024)
This study employs a quantitative approach to investigate the causal relationships between Quality of Work Life (QWL), Organizational Citizenship Behavior (OCB), Work Motivation, and Employee Performance within a sample of 50 respondents from a tollroad operator. The findings reveal that QWL, OCB, and work motivation each have a significant positive impact on employee performance. These results underscore the importance of creating a conducive work environment, promoting positive organizational behavior, and motivating employees to achieve higher performance levels. This study contributes to the understanding of factors that drive employee performance and offers practical implications for organizations aiming to improve their workforce's effectiveness and productivity. Highlights: Quality of Work Life, OCB, and Work Motivation positively influence Employee Performance. Quantitative approach used to analyze the causal relationships. Practical implications for organizations seeking to enhance workforce effectiveness. Keywords: Employee Performance, Quality of Work Life, Organizational Citizenship Behavior, Work Motivation, Causality